Perbandingan Efektivitas Penggunaan Teguran Dan Ajakan Dalam Pengumuman Masjid - Siti Maesyaroh,, Syarah (Jurnal Syntax Fusion, 2024)
The mosque announcement is an important communication instrument to remind worshippers about worship activities and mosque regulations. This study aims to identify the influence of the use of words reprimand and invitation in mosque announcements on the perception and behavior of worshippers, as well as to prepare recommendations for mosque administrators in choosing more effective words. The research used a qualitative approach with a case study design in Mosque X, involving 6 mosque administrators and 12 worshippers as participants. Data was collected through in-depth interviews, participatory observations, and analysis of announcement documents, then analyzed using thematic analysis. The results showed that announcements with an invitation approach were more effective than reprimands in increasing congregational participation, with an average attendance rate of 35 percent higher. Invitational announcements generate positive perceptions in all pilgrims and arouse stronger intrinsic motivation, while reprimands cause feelings of discomfort in 75 percent of pilgrims. This study concludes that an inclusive, positive, and harmonious approach to invitation that is in harmony with theological and cultural values is more optimal in achieving the goal of mosque communication. Research recommends the use of the call-to-action approach as the primary strategy, with reprimands only used in situations that require assertiveness.